Predictors affecting the severity of irrigated maize due to fall armyworm (Spodoptera frugiperda, Smith) and its natural enemies in Bako-Tibe district, central Ethiopia - Abera Aboset Bedasa; Emana Getu Degaga (Scientific African)
The fall armyworm, Spodoptera frugiperda Smith was first reported in Ethiopia in 2017. Since then, it is spreading throughout the country and caused substantial damage to maize farms, and threatening food security. Objectives of the study were to assess predictors influencing the severity level of irrigated maize due to S. frugiperda and to give an account of possible local natural enemy communities in irrigated maize farms in the Bako-Tibe district of central Ethiopia. Irrigated maize farms were selected purposively. Five randomly selected plots sampled in a ''W'' design, each comprising 10 consecutive plants. The study performed in longitudinal approach. The result shows farms and maize growth stages were among the first and second-best significant indicators of severity level, respectively. Farmers utilized various agronomic activities, such as varying the dates of sowing. The infestation rate, larvae density, and severity of irrigated maize plants ranged in values from 58.0 to 98.0 %, 1.1 to 5.69, and 2.35 to 8.47 respectively. There were no longer any early-planted maize farms. From plants seeded between mid-December and March, green ears of maize were harvested. Visually identified S. frugiperda predators include weaver birds, frogs, and insects belong to order Coleoptera, Dermaptera, Hemiptera and Hymenoptera. To minimize S. frugiperda damage level farmers’ sprayed insecticides, 80 % belonged to WHO toxic class II, which are moderately hazardous insecticides. Vernonia spp. and Justice schimperina used as botanical source bio-pesticides. Based on results, we suggest that frequent irrigation, late planting (starting in December), intercropping, and fertilizer application are effective S. frugiperda impact mitigation techniques for the cultivation of irrigated maize.